SOURCES FOR FINANCING THE ENVIRONMENTAL TRANSFORMATION OF PRODUCTION AS A COMPONENT OF THE INNOVATIVE ENTERPRISE DEVELOPMENT - DEMCHENKO, Kseniia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In article was presented the distribution of expenditures on innovation among industrial enterprises belonging to the category of innovatively active. It was emphasized the insufficient level of research and development due to lack of financial support. The main directions of innovation activity of industrial enterprises are focused on forced renewal of capital assets, the influence of the lack of funding on the innovative activity of business entities is revealed. Author emphasizes the need to develop recommendations for finding sources of funding to ensure the innovative transformation of industrial enterprises. It was analyzed the main sources to finance innovation activities of ukrainian industrial enterprises. It was found that the main source of financing the innovative development of enterprises is their own funds. The study examined the possibilities of using borrowed funds and explored the role of bank lending in ensuring innovation. Particular attention is paid to project finance as a mixed type of financing.Based on the knowledge about the financing of innovations by industrial enterprises were identified the features of funding for ecological modernization of production by cement producers in Ukraine. It is determined the significant role of foreign capital in the process of ecological transformations of enterprises in the industry.The main trends and prospects for funding innovative projects for cement industry enterprises are highlighted. Proposals for optimizing the structure of sources of financing for innovative development for cement producers are developed. The proposed sources of financing for the ecological transformation of production fall into different categories, including government funding, the use of investment funds resources and participation in project financing.
Keywords: financing; innovation; enterprise; entrepreneurship; environmental innovations; sustainable development; ecological modernization; ecological; project; production